LEGAL REGULATION OF THE USE OF ARTIFICIAL INTELLIGENCE IN THE DEVELOPMENT OF THE TOURISM INDUSTRY : DOI: 10.5937/etp2402115T - Trifunović, Ivan; Spalević, Žaklina; Marković, Sanja (Ekonomija - teorija i praksa, 2024)
Tourism has become a mass industry that attracts over a billion people worldwide annually. With the increasing application of artificial intelligence, technology is accelerating changes in tourism, enhancing customer service, operational efficiency, and supporting sustainable practices. Therefore, the aim of this paper is to provide an overview of the impact of Generative Artificial Intelligence (GAI) on the hospitality and tourism industry. Through the analysis of various aspects of GAI application in this sector, the paper explores potential benefits and challenges that this technology brings for companies, stakeholders, and users. Additionally, the paper addresses legal and ethical aspects of GAI usage, particularly concerning data protection, privacy, and compliance with relevant laws and regulations. A special focus is on the REFLECT model, which offers a holistic approach to the use of artificial intelligence, enabling companies to better understand and manage the implementation of this technology.